Marvel Cinematic Universe in translation: a study of intertextual coherence and inter-filmic discourse - Rauhala, Elina (My University, 2016)
The primary objective of the present thesis was to determine the extent of intertextual coherence and inter-filmic discourse retained in the Finnish DVD subtitles of the first twelve feature films set in the Marvel Cinematic Universe and ten episodes of the first season of Agents of S.H.I.E.L.D., a transmedia extension of the MCU. The cinematic world of Marvel was chosen as research data in this study for the inherence, abundance, and conspicuousness of its intertextuality. Two categories through which to retain intertextual coherence in translation were set as the premise of the study: 1) the consistent application of the same form of MCU-related proper names in translation and 2) the retention of MCU-related allusions in translation when the retention of the allusion is a strategic choice. The data was collected and analyzed primarily in this juxtaposition. The examination of the gathered data and the set research questions necessitated the division of audiovisual allusions into three categories: verbal visual allusions, secondary spoken allusions, and primary spoken allusions, the last of which was further divided into ambiguous and unambiguous types. Because of their qualitative inadequacies, unambiguous primary spoken allusions were not eligible as data in the present study. 33.3 percent of the proper names qualified as data were translated consistently in each installment they were referenced. In terms of allusions, 76.2 percent of the qualified source-text instances were retained in translation. The results indicate that intertextual elements are more easily identified and retained within the context of one narrative than when this requires the observation of multiple connected narratives as one interwoven universe.